PERIODISASI DAN FAKTOR-FAKTOR PERUBAHAN SPASIAL DI DUSUN BRAYUT DALAM KONTEKS DESA WISATA - , LATIFATUR ROCHIMAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Dusun Brayut has many uniqueness such as sabuk inten as its physical feature, traditional buildings, and the incident of Dutch Military Agression II which happened here. Dusun Brayut which later known as âDesa Wisata Brayutâ was the first tourism village in Kabupaten Sleman stated on August 14st 1999. The new function of tourism in Brayut was triggering a spatial adaptation process which in the other hand can reduce its village scenery. By this reason, this research mainly focuses on the spatial changes of Dusun Brayut and the factors affecting those changes. This research utilizes qualitative-inductive and explorative approach as its method. The data and information was gathered from literature review, in-depth interview, and field observation. The informant for this research chosen with purposive and snowball sampling method which was resulting 27 informants from 9 different groups. After the process of data gathering and analyzes, the result then confirmed its validity by utilizes member check method. This research resulted that the spatial changes in Dusun Brayut can be divided into six periods. These periods are shaping of Dusun Brayutâs spatial pattern (1940-1975), basic infrastructure development (1983-1997), tourism village making (1998-2001), the transition period (2002-2004), tourism village development (2006-2011), and the new industrial land use function (2010-2014). Furthermore, those each period has its own alteration factors with the main factor of the spatial changes in Dusun Brayut was not caused by the new function of the tourism village but the local social condition of Brayut called âguyubâ.